Heat transfer and entropy generation analyses of nanofluids in helically coiled tube-in-tube heat exchangers. (February 2016) - Huminic, Gabriela; Huminic, Angel
Abstract: In this work, a three-dimensional analysis is used to study the heat transfer and entropy generation inside a helically coiled tube-in-tube heat exchanger in laminar flow regime using two different types of nanofluids. Overall heat transfer coefficient, effectiveness, Nusselt number, and entropy generation of helically coiled tube-in-tube heat exchanger were investigated considering the nanoparticle volume concentrations between 0 and 2.0 vol.%. The mass flow rate of the nanofluid from the inner tube was kept and the mass flow rate of the water from the annulus was set at either half, full, or double the value. The present contribution is a companion paper of Huminic and Huminic [1]. The numerical results reveal that the use of nanofluids in a helically coiled tube-in-tube heat exchanger improves the heat transfer performances. Thus, the maximum effectiveness was 91% for 2% CuO nanoparticles and 80% for 2% TiO2 nanoparticles. Also, the increase of nanoparticles volume concentration leads to the Nusselt number increase and the reduction of the entropy generation due heat transfer effects, the viscous effects to entropy generation being negligible.